Moderating Effect of Ownership Structure on the Relationship between R&D Investment and Corporate Performance - Yujun Miao, Yongyan Luo (Design Engineering, 2020)
This thesis takes the panel data of A-share manufacturing companies listed on the Shanghai Stock Exchange and Shenzhen Stock Exchange from 2014 to 2018 as a sample for research. Through empirical research, it is expected that manufacturing companies will have further thoughts on the corporate governance of the ownership structure and put forward some reasonable suggestions. The main research methods used in this paper are Pearson correlation coefficient, multiple regression and hierarchical regression. These methods are aimed to analyze the correlation of R&D investment and corporate performance, and the correlation between ownership structure and firm performance, as well as whether corporate structure will produce moderating effect on the relation among R&D investment and enterprise performance, and the direction of moderating. Research results show that the R&D investment of the sample businesses will significantly increase the performance of the company. In the correlation of R&D investment and corporate performance, ownership concentration has a positive moderating effect, but the equity balance degree has a negative moderating effect. Therefore, enterprises can increase research and development investment and maintain a proper ownership structure to improve corporate performance.